2016
DOI: 10.1097/scs.0000000000003004
|View full text |Cite
|
Sign up to set email alerts
|

Bimaxillary Oral Focal Mucinosis

Abstract: Oral focal mucinosis is considered as oral counterpart of cutaneous focal mucinosis. The preoperative diagnosis of mucinosis is almost impossible because of its rarity and clinical similarity to other lesions of various etiologies. The histological diagnosis of oral mucinosis is important to better understand the etiopathogenesis, treatment modalities, and any recurrence of the lesion besides differentiating from the other soft tissue lesions.The purpose of this paper is to report the first case of bimaxillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The treatment of choice in this patient was complete surgical excision of her soft tissue lesion, which is the accepted method for OFM in previously noted case reports 5 6 8. There are rare reports of recurrence, with one recurrence noted due to incomplete excision 14.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The treatment of choice in this patient was complete surgical excision of her soft tissue lesion, which is the accepted method for OFM in previously noted case reports 5 6 8. There are rare reports of recurrence, with one recurrence noted due to incomplete excision 14.…”
Section: Discussionmentioning
confidence: 82%
“…This case report depicts the lesion of OFM on the left mandible gingiva of an adolescent patient. The aetiology of this lesion is unclear, though a study by Neto et al suggested trauma could be the predisposing factor 5. Previous studies have mentioned overproduction of hyaluronic acid by surrounding fibroblasts in the stroma, which intrudes into the surrounding collagen 1–4 10.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other anatomical sites included buccal mucosa, tongue, retromolar trigone, and lips. There were also two rare cases of bilateral lesions on the palate 33,34 . Clinically, OFM presented as a submucosal sessile or pedunculated nodule, measuring from 0.5 to 4.5 cm (mean 1.10 cm, SD 0.72) and soft to firm in consistency.…”
Section: Resultsmentioning
confidence: 99%